Karakteristik Pasien dan Tata Laksana Infeksi Malaria di RSUP Prof. dr. I.G.N.G. Ngoerah Denpasar Tahun 2019-2023 - I Dewa Gede Agung Suta Ariwangsa; Harris Hardian; I Made Susila Utama (MEDICINUS, 2025)
Introduction: Malaria remains a major public health concern, affecting resident and travellers to endemic areas. Severemalaria is a complication of infection that can lead to poor outcomes when late to be diagnosed. The use of artemisininRESEARCH22 VOL. 38 ISSUE 12, DECEMBER 2025derivatives or artemisinin-based combination therapy (ACT) has been reported to improve outcomes and survival in malaria patients. Methods: This was a descriptive study. Data were collected retrospectively from medical records ofpatients treated at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar from 2019 to 2023. Descriptive analyses were conducted to summarize patient's characteristics, infection etiology, malaria severity, and treatment outcomes. Results: A total of37 malaria cases were treated at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar between 2019 and 2023. The mean age of patients was 29.85 years, and the majority were male (78.37%). Plasmodium vivax was identified as the most commonetiologic agent, in 19 cases (51.35%), followed by Plasmodium falciparum in 17 cases (45.94%), and Plasmodium malariae in 1 case (2.7%). Severe malaria was diagnosed in 9 cases (24.32%), predominantly caused by P. falciparum (7 cases,94.5%). Jaundice and renal dysfunction were the most frequent clinical findings in severe malaria, seen in 7 (77.77%) and 4 (44.44%) cases, respectively. The most common treatment regimens were 3-day dihydroartemisinin-piperaquine (DHP) plus 14-day primaquine in 10 patients (48.64%), and 3-day DHP plus 1-day primaquine in another 10 patients (27.02%).Intravenous artesunate followed by 3-day DHP and 3-day primaquine was administered to 7 patients (18.91%); artesunate followed by DHP and 1-day primaquine to 1 patient (2.7%), and artesunate followed by DHP alone to 1 patient (2.7%). Nodeaths were reported during treatment. Discussion: Severe malaria was identified in 9 out of 37 cases (24.3%), with P. vivax being the most common malaria species overall. Although severe malaria is typically associated with P. falciparumand P. vivax, this study also reported one severe case caused by P. malariae. Jaundice was the most common clinical presentation, often accompanied by renal impairment. All patients received artemisinin-based combination therapy andachieved complete recovery at the end of treatment. Conclusion: Severe malaria occurred in one-quarter of malariacases, with P. falciparum being the most frequent cause. Jaundice and renal dysfunction were the most common clinical manifestations. All patients recovered and were discharged from the hospital.